Scientific Learning Approach: Improving Student Learning Outcomes on The Concept of Measurement in Elementary Schools - Ishabu, La Suha; Takaria, Johannis; Heatubun, Hana (PEDAGOGIKA: Jurnal Pedagogik dan Dinamika Pendidikan, 2025)
The purpose of this study was to determine the improvement of student learning outcomes through a scientific approach. The method used is descriptive with the type of Classroom Action Research (CAR). This study involved 13 fifth grade elementary school students as subjects and analyzed the improvement of learning outcomes using N-gain. The results of the study showed that in cycle I, 8 students or 61.6% did not complete the learning and cycle II, 13 students or 100% achieved learning completion. The improvement of student learning outcomes using a scientific approach was obtained that in the high category, there were 5 students with an average N-gain of 0.78, in the medium category, 7 students with an N-gain of 0.52, and in the low category, 1 student achieved an improvement with an average N-gain of 0.20. This improvement is due to the effective use of the scientific approach. The scientific approach contributes to developing students' abilities to conduct experiments and observe directly with measuring instruments, so that students gain real experience in learning mathematics.